Psychological Empowerment Mediates the Effect of Workplace Wellbeing on Readiness to Change - Munawaroh, Munawaroh; Fitriati, Rachma (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2022)
This study aims to see the readiness of individuals in dealing with changes that occur in the environment, especially in the workplace. In this study, data was obtained by distributing questionnaires to 200 respondents who were selected using a simple random sampling technique. The research data that has been collected is then analyzed descriptively and quantitatively. The data analysis technique was carried out in three stages, namely the inner model, outer model, and hypothesis testing. Using Structural Equation Modeling Partial Least Square (SEM-PLS), the findings of this study indicate that exogenous variables (workplace welfare and psychological empowerment) have a positive and significant effect on endogenous variables (individual readiness to change) in educators at the Universitas Negeri Jakarta Diploma level. The results also prove that psychological empowerment can be a mediator between the effect of workplace well-being on individual readiness to change in a positive and significant way.